STUDI DESAIN ALUR GAS PADA ANODA PLAT BIPOLAR DAN PENGARUHNYA TERHADAP PERFORMA PEMFC BERDASARKAN HASIL EKSPERIMEN - Indriyati, -; Pujiastuti, Sri; Lazuardi, -; Isya, Nini (LIPI Press, 2011)
The effect of the anode fl ow fi eld design on the performance of Proton Exchange Membrane Fuel Cell (PEMFC) with an active area 9 cm2 was investigated experimentally. 3-channel serpentine, 5-channel serpentine and modifi - cation of serpentine-parallel fl ow fi elds has similar channel cross section, 1.35 mm for channel width, 0.55 mm for channel depth, and 0.7 mm for the land between channels. They were tested with hydrogen fl ow rate of 50 ml/min, oxygen flow rate of 250 ml/min, pressure 1.5 Bar, and dew point temperature 80C at 100% relative humidity. The experimental results obtained from measurement of current (I) and potential (V) indicated that 3-channel serpentine exhibited higher performance than others even though it was not so significant. At current density of 20 mA/cm2, modification serpentine-parallel design showed signifi cant potential drop, probably due to turbulence gas flow inside the channel. Open circuit voltage (OCV) for 5-channel serpentine was 6% lower than those two designs. Finally, it was demonstrated that the maximum power of the fuel cell stack were 146 mW, 139 mW, 132 mW for 3-channel serpentine, 5-channel serpentine, and modifi cation parallel-serpentine, respectively.